2008
DOI: 10.1093/ajcn/88.2.465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium citrate supplementation or increased fruit and vegetable intake on bone metabolism in healthy postmenopausal women: a randomized controlled trial

Abstract: Background: Alkali provision may explain why fruit and vegetables benefit bone health. Objective: We aimed to determine the effects of alkali-providing potassium citrate (double-blind) and fruit and vegetable intake (single-blind) on bone turnover over 2 y. Design: We conducted a randomized placebo-controlled trial in 276 postmenopausal women (aged 55-65 y). Women were randomly assigned to 4 groups: high-dose potassium citrate (55.5 mEq/d), low-dose potassium citrate (18.5 mEq/d), placebo, and 300 g additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(182 citation statements)
references
References 33 publications
5
172
1
4
Order By: Relevance
“…The bone loss observed for NE Scotland for the 24-h urine subset was similar to that already reported for the full data set. 11 This is the first time the Californian data relating to bone health have been shown. The percentage bone loss was less compared with NE Scotland, which may be because the Californian women were more than 5 years past the menopause.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The bone loss observed for NE Scotland for the 24-h urine subset was similar to that already reported for the full data set. 11 This is the first time the Californian data relating to bone health have been shown. The percentage bone loss was less compared with NE Scotland, which may be because the Californian women were more than 5 years past the menopause.…”
Section: Discussionmentioning
confidence: 97%
“…Subjects for this retrospective study were a subset of postmenopausal women living in the Aberdeen area who provided 24-h urine samples during a dietary intervention trial. 11 Exclusion criteria for the original study, which was registered at http://www.controlled-trials.com as ISRCTN86186352, were the lowest 10% of estimated dietary acidity (NEAP calculated from the food frequency questionnaires), 33 and any condition or medication that would affect bone metabolism and potassium-sparing diuretics. Women taking other types of diuretics or hypertension tablets and women on thyroxine treatment provided their thyroid function was stable (as assessed by free T4 and TSH) and their dose had not changed in the year before study entry were included in the study.…”
Section: North East (Ne) Scotlandmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects completed 4-day estimated portion size food diaries and the FFQ 9 months apart as a measure of compliance in a fruit and vegetable intervention trial. (8) Assessment of potential confounders…”
Section: Assessment Of Diet and Flavonoid Intakesmentioning
confidence: 99%
“…A recent 2-year randomized, controlled trial found that supplementation with potassium citrate or three additional portions of fruit and vegetables a day did not reduce bone turnover or increase BMD, suggesting that any long-term benefits of fruit and vegetable intake on bone are not due to the provision of alkaline salts. (8) Animal studies have shown that ovariectomy-induced bone resorption can be inhibited by onions and other vegetables commonly eaten by humans (9) and that this effect is independent of their base-balancing properties, (10) indicating that the protective effects of fruit and vegetables may be found in the nutrients they contain.…”
Section: Introductionmentioning
confidence: 99%